Adapting teaching strategies to global and analytic learning styles by real world engineering projects - Daneti, Marllene (IEEE Global Engineering Education Conference, 2014)
This paper investigates the way by which teaching strategies at the freshmen level in electrical engineering could be adapted, given the fact that the dynamic of the target group evolves fast and it's characteristics differ considerably from the classic typology. Approaching the target-group, taken into account their global or analytic learning style, could contribute to this goal. A comparative study of some real world engineering projects from the literature is conducted. It is observed that by using subjects from the real world, a better adaptation of the whole range of teaching strategies to the given human resource is attained, which in turns facilitates achievement of the key skills at all levels.